Where are all the gay fathers?: Reflections on recruiting gay fathers as participants in leisure research. Issue 3 (3rd May 2020) - Bauer, Michelle E. E.; Giles, Audrey R.
ABSTRACT: There is a dearth of understanding of gay fathers' perspectives on leisure studies topics. If researchers are to conduct research that better reflects all fathers, it is important to gain insights into recruiting gay fathers, and to ensure that gay fathers know that their perspectives are needed and desired. Thus, in this research note, we highlight two important reflections on the difficulties we encountered when attempting to recruit gay fathers as research participants: (1) Heteronormativity exists in leisure studies and it is problematic for the recruitment of gay fathers; and (2) understaffed organisations are at times unable to help recruit gay fathers for research. Researchers who work with gay fathers may draw on our reflections to overcome similar difficulties that they may face. It is our hope that our reflections may contribute towards achieving the important social justice goal of including gay fathers in leisure studies.